DNA FINGERPRINTING OF COMMERCIAL MUSHROOMS BY ISSR AND SSR MARKERS FOR GENETIC DISCRIMINATION - M.P. PRASAD; K. AGARWAL (International Journal of Pharma and Bio Sciences, 2013)
Research for new improved varieties, with high increase in yields and quality with disease resistance is required today to make mushroom production highly productive.Increasing the yield and quality of crops as well as resistance to diseases are the primary goals for mushroom breeders and mushroom research. Breeders now use DNA molecular markers to identify and select specific genes to locate superior traits. Thus, utilizing molecular markers to explore traits from wild isolates can expand the genetic base of the cultivated mushrooms. In current research eleven commercial mushrooms samples namely 1) A. bisporus (Button), 2) A. bisporus (Portobello), 3) P. eryngii (King Oyster), 4) L. edodes (shiitake), 5) H. tessellatus (Brown Shimeji), 6) H. tessellatus (White Shimeji), 7) F. velutipes (Enoki), 8) P. ostreatus (Oyster), 9) P. djamor (Pink Oyster), 10) C. indica (Milky), and 11) P. florida (Florida Oyster) were used. The ISSR and SSR markers were used for discrimination of the selected mushroom samples. The results of ISSR markers construe that some samples might originate from a single strain. The SSR amplified alleles can be used as marker for identification of mushrooms. The information on the genetic relatedness presented here will be useful for breeding programmers for detection of duplicate sample and selection of parent strains to avoid inbreeding depression.